2016
DOI: 10.1080/15583724.2015.1091776
|View full text |Cite
|
Sign up to set email alerts
|

Melt Extrusion Encapsulation of Flavors: A Review

Abstract: Encapsulation of flavor and aroma compounds has been largely explored in order to meet appraisal demands from consumers by improving the impact of flavor during the consumption of food products. Even though several techniques have been used for encapsulating volatile compounds, i.e., spray drying, fluidized bed coating, coacervation, and melt extrusion, those most frequently used in the food industry are spray drying and melt extrusion. In this article, the different techniques of encapsulation of flavors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 82 publications
0
14
0
3
Order By: Relevance
“…Not to mention that maltodextrins are odor-, color-and tasteless so they appear as the best option to be employed as encapsulating agents either by spray-drying or twin-screw extrusion. Nowadays, maltodextrins are used as the main ingredient rather than additive for the elaboration of bio-based materials by melt extrusion (Bouquerand, Maio, Meyer, & Normand, 2008;Castro et al, 2016;Tackenberg, Marmann, Thommes, Schuchmann, & Kleinebudde, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Not to mention that maltodextrins are odor-, color-and tasteless so they appear as the best option to be employed as encapsulating agents either by spray-drying or twin-screw extrusion. Nowadays, maltodextrins are used as the main ingredient rather than additive for the elaboration of bio-based materials by melt extrusion (Bouquerand, Maio, Meyer, & Normand, 2008;Castro et al, 2016;Tackenberg, Marmann, Thommes, Schuchmann, & Kleinebudde, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The large surface area per unit mass of nano-sized biomaterials may increase their functionality, biological activity, or allow the release of compounds at controlled rates [ 74 ]. The structure also has a relevant influence, as structures composed of various layers generally present higher stability and a more sustained release pattern [ 51 , 75 ].…”
Section: Insights Into the Selection Of Encapsulation Methods And Wmentioning
confidence: 99%
“…Regarding the type of wall materials, food-grade biopolymers must be used for food applications; these include carbohydrates, gums, proteins, and lipids [ 71 , 76 ]. Factors to be taken into account, regarding their use, are their technological properties (solubility, film-forming ability, emulsifying capacity, hygroscopicity, viscosity, gelling ability, melting point), physical state (amorphous, glassy), organoleptic properties (color, odor, taste), and physico-chemical compatibility with the core material [ 52 , 75 ]. In this connection, it is common to use surface-active compounds as emulsifiers to improve compatibility [ 58 ].…”
Section: Insights Into the Selection Of Encapsulation Methods And Wmentioning
confidence: 99%
“…They found that not only was it possible, but the probiotic powder had an additional plasticizing effect on the extrudates. Melt extrusion and its earlier variant, melt injection has found extensive use as an encapsulation technique especially for fragrances and flavors due to the lower energy requirement, minimal emission of odor fouled exhaust, no requirement for solvent, and possibility for large volume encapsulation [40]. In addition, extrusion encapsulations impart longer stability on flavors and lower degradation for enzymes, when compared to other encapsulation methods like spray drying [39].…”
Section: Extrusionmentioning
confidence: 99%